At the Borders Between Translation and Parody: Lydia Davis’s Story about Marie Curie - Evans, Jonathan (TTR)

(untitled) (Association canadienne de traductologie, 2012)
Lydia Davis’s story “Marie Curie, So Honorable Woman” poses a number of questions related to its status. It is presented as a story, but it is constructed from translations of extracts of Françoise Giroud’s Une femme honorable, which Davis had previously translated as Marie Curie: A Life. This article analyses how the story questions the borders between translation and other forms of intertextual writing. First it analyses how the text was presented in its magazine publication in McSweeney’s Quarterly Concern under the title “Translation Exercise #1: Marie Curie, Honorable Woman.” It then discusses how Davis’s use of abridgement in this story and other stories is similar to translation before analysing the translations in the story, which exaggerate the interference from the source language. Along with the choice of extracts, this translation strategy suggests that the story is a parody. It follows the legal and literary definitions of the parody because it exhibits a critical distance from its source text. But it is parody of a text which is not well known in the target culture and so it is unlikely to be recognised as a parody by readers. As a text, “Marie Curie, So Honorable Woman” questions the relationship between translation and parody, but it also questions ideas about representation through its style and its relation to its source text.